Future of power - "Nye, Joseph S." (New York, 2011)
In the era of Kennedy and Khrushchev, power was expressed in terms of nuclear missiles, industrial capacity, numbers of men under arms, and tanks lined up ready to cross the plains of Eastern Europe. By 2010, none of these factors confer power in the same way: industrial capacity seems an almost Victorian virtue, and cyber threats are wielded by non-state actors. Politics changed, and the nature of power--defined as the ability to affect others to obtain the outcomes you want--had changed dramatically. Power is not static; its story is of shifts and innovations, technologies and relationships. Joseph Nye is a long-time analyst of power and a hands-on practitioner in government. Many of his ideas have been at the heart of recent debates over the role America should play in the world: his concept of "soft power" has been adopted by leaders from Britain to China; "smart power" has been adopted as the bumper-sticker for the Obama Administration's foreign policy. This book is the summation of his work, as relevant to general readers as to foreign policy specialists. It is a vivid narrative that delves behind the elusive faces of power to discover its enduring nature in the cyber age.
Keywords: "Power (Social sciences), Relations internationales. - Po"